Characterization of the SiO2 film deposited by using plasma enhanced chemical vapor deposition (PECVD) with TEOS/N2/O2 - Zarchi, Meysam; Sanjari, Maryam Zare; Ahangarani, Shahrokh (Metallurgical and Materials Engineering, 2013)
The purpose of this study was to examine how certain parameters like temperature, pressure, and gas composition affect the characteristics of SiO2 film by Plasma Enhanced Chemical Vapor Deposition (PECVD). We used of low temperature and an inductively coupled plasma (ICP) for various with gas mixtures of TEOS/N2/O2 at a given RF power and dc bias voltage. For the gas mixture with 40 sccm of N2 in TEOS, 100 standard cubic centimeters per minute (sccm) of N2, and 500 sccm of O2, transparent and scratch-resistant SiO2 could be deposited with a deposition rate of 30 nm/min when RF power of 500 W and a dc-bias voltage of 350V were applied. The characteristics of the deposited SiO2, such as the composition, the binding energy, etc. were compared with the SiO2 deposited by using thermal CVD and evaporation. It was found that the SiO2 deposited by PECVD with TEOS/N2/O2 exhibited properties typical of SiO2 deposited applying thermal CVD and evaporation. The surface roughness of the 100 nm-thick SiO2 deposited by PECVD was similar to that of the substrate.